Risk Factors of Moderate and Severe Malnutrition in Under Five Children at East Nusa Tenggara - Kadek Dwi Ariesthi; Kadek Tresna Adhi; Dewa Nyoman Wirawan (Universitas Udayana, 2015)
Background and purpose: East Nusa Tenggara is the province with the prevalence of moderate and severe malnutrition second highest in Indonesia, amounting to 29.4%. The aim of this study was to identify risk factors of moderate and severe malnutrition among under five children at East Nusa Tenggara. Methods: A case control study was carried out at North Kodi Subdistrict, Southwest Sumba District, East Nusa Tenggara, consisted of 38 moderate and severe malnutrition under five children as cases and 76 healthy under five children as controls. Independent variables were maternal and child factors, feeding and health care practises and sanitation. Data were collected by conducting interviews and analysed using Stata SE 12.1. Bivariate analysis was done to calculate crude odd ratio and logistic regression was done to calculate adjusted odd ratio. Results: Bivariate analysis showed that family income, frequency of illness, mother’s knowledge, frequency of visiting health care centres, number of children , and quality of drinking water supply were risk factors of moderate and severe malnutrition among under five children. Multivariate analysis showed that significant risk factors were frequency of illness (adjusted OR=35,4; 95%CI:4,8–256,8), family income (adjusted OR=14.8; 95%CI: 2.1-100.9), mother’s knowledge (adjusted OR=9.8; 95%CI: 1.4-66.1), frequency of visiting posyandu (adjusted OR=9.0; 95%CI: 1.6-50.7) and source of drinking water (adjusted OR=7.1; 95%CI: 1.1-45.5). Conclusion: Frequency of illness, family income, mother’s knowledge, frequency of visiting posyandu and source of drinking water were predominate risk factors of moderate and severe malnutrition at North Kodi Sub-district, Southwest Sumba, East Nusa Tenggara.